The Financial Implications of Pancreatic Surgery: The Hospital Is the Big Winner, Not the Surgeon! - Nitzan Zohar, MD; Avinoam Nevler, MD; Sean P. Maher; Matthew C. Rosenthal; Florence Williams; Wilbur B. Bowne, MD, FACS; Charles J. Yeo, MD, FACS; Harish Lavu, MD, FACS (Annals of Surgery Open)
Background:. High-volume pancreatic surgery centers require a significant investment in expertise, time, and resources to achieve optimal patient outcomes. A detailed understanding of the economics of major pancreatic surgery is limited among many clinicians and hospital administrators. A greater consideration of these financial aspects may in fact have implications for enhancing clinical care and for a broader sustainability of high-volume pancreatic surgery programs. Methods:. In this retrospective observational study, patients who underwent pancreaticoduodenectomy (PD), total pancreatectomy, or distal pancreatectomy at one academic medical center during the fiscal year 2021 were evaluated. Detailed hospital charges and professional fees were obtained for patients using the Qlik perioperative database. Clinical data for the study cohort were gathered from a prospectively maintained, IRB-approved pancreatic surgery database. Charges for the 91-day perioperative period were included. A P < 0.05 was considered significant. Results:. During the study period, 159 evaluable patients underwent 1 of 3 designated pancreatic resections included in the analysis. Ninety-seven patients (61%) were diagnosed with adenocarcinoma and 70% (n = 110) underwent PD. The total charges (combined professional and hospital charges) for the cohort encompassing the entire perioperative period were $20,661,759. The median charge per patient was $130,306 (interquartile range [IQR], $34,534). The median direct cost of care was $23,219 (IQR, $6321) and the median contribution margin per case was $10,092 (IQR, $22,949). The median surgeon professional fee charges were $7700 per patient (IQR, $1296) as compared to $3453 (IQR, $1,144) for professional fee receipts (45% of the surgeon charge). The differences between the professional fee charges and receipts per patient were also considerable for other health care professionals such as anesthesiologists ($4945 charges vs $1406 receipts [28%]) and pathologists ($3035 charges vs $680 receipts [22%]). The surgeon professional fees were only 6% of the total charges, while the professional fees for anesthesiology and pathology were 4% and 2% of the total charges, respectively. Supply charges were 3% of the total charges. Longer operative time was correlated with increased hospital and anesthesia charges, without a significant increase in surgeon charges (P < 0.001, P < 0.001, and P = 0.2, respectively). Male sex, diabetes, and low serum albumin correlated with greater total hospital charges (P = 0.01, P = 0.01, and P = 0.03, respectively). Conclusions:. The role of the surgeon in the perioperative clinical care of major pancreatic resection patients is crucial and important and is by no means limited to the operative day. Nevertheless, in the context of the current US health care system, the reimbursement to the surgeon in the form of professional fees is a relatively small fraction of the total health care receipts for these patients. This imbalance necessitates a substantial financial partnership between hospitals and their pancreatic surgery units to ensure the long-term viability of these programs.